Perceived performance : the only kind that really matters (O'Reilly Media, 2017)
"Perceived performance, in the end, is the only performance that truly matters. If what we make doesn't feel fast, then no amount of optimization counts. Eli Fitch breaks down the psychology of how users perceive time and how we can combine that knowledge with clever use of animation, unconventional event listeners, and predictive design to make our experiences seem faster than they actually are."--Resource description page